Relación entre las variables de los estilos liderazgo con los resultados de productividad humana en una empresa del sector floricultor. - Maldonado Suárez, Jhon Édinsson; Pardo, Leidy Johana; Pinzón Arias, Arthur Steven; Cuesta Hoyos, Katherine (Corporación Universitaria Minuto de Dios, 2023)
La presente investigación aborda las relaciones existentes entre el estilo de liderazgo auto percibido y la productividad humana auto percibida de las personas responsables de los procesos productivos en una de las fincas de una empresa floricultora del municipio de Madrid con 650 trabajadores. Al analizar la realidad de la empresa estudiada, se hallaron diferencias en los resultados de los responsables de los procesos productivos, es por ello por lo que se plantea el estudio de las causas de dichas disparidades desde la comprensión de los estilos de liderazgo. Se utilizó una metodología de investigación no experimental con un alcance correlacional mediante el método deductivo cuantitativo. El estudio se aplicó a toda la población de líderes a cargo de actividades relacionadas con la producción, en total 32 personas. Se empleó un cuestionario que consolida tres instrumentos previamente validados para establecer los estilos de liderazgo y medir la productividad humana: el cuestionario de liderazgo gerencial de Blake y Mouton, el cuestionario multifactorial de liderazgo de Bass y Avolio (MLQ) y el instrumento de medición de la productividad humana (IMPH) de Cequea.

This research examines the relationship between self-perceived leadership style and self-perceived human productivity among individuals responsible for the production processes in a flower farming company in the municipality of Madrid. Upon analyzing the reality of the company studied, differences were found in the results of the individuals responsible for the production processes. Therefore, the study aims to understand the causes of these disparities through the comprehension of leadership styles. A non-experimental research methodology with a correlational scope was employed, utilizing the quantitative deductive method. The study was conducted on the entire population of leaders in charge of production-related activities, totaling thirty-two individuals. A 132-statement Likert scale questionnaire was applied, consolidating three previously validated instruments to establish leadership styles and measure human productivity. The instrument combines Blake and Mouton's Managerial Grid Questionnaire, Bass and Avolio's Multifactor Leadership Questionnaire (MLQ), and Cequea's Human Productivity Measurement Instrument (IMPH). It was found that two types of leaders were identified: transactional and transformational. Both leadership styles share characteristics and are correlated within the studied organization, which is why no differences were found in the levels of human productivity between the two leadership styles. Significant correlations were also found between variables measuring leadership characteristics and variables measuring human productivity, which facilitated the development of a linear regression model to predict an individual's productivity level based on the measurement of their leadership skills
Determinar la relación entre las variables de los estilos liderazgo de las personas que coordinan las actividades de producción con los resultados de productividad humana de la empresa Sunshine Bouquet Company, en la finca Gascuña del municipio de Madrid
Keywords: Liderazgo; Estilos de liderazgo; Sector floricultor; Floricultura; Productividad humana; Producción; Leadership; Leadership styles; Floriculture sector; Human productivity; Production; Liderazgo; Productividad agrícola; Floricultura